Ocena możliwości zwiększenia dochodów gmin z mienia nieruchomego - Marona, Bartłomiej (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Realties located on gmina's territory, in peculiar municipal real estate, make up the significant source of gmina's income. The level of incomes and gmina's rate of development is therefore decided by: rational decisions in field of real estate management, professionalism of managers, and reliable control of effective allocation of property. The efficiency of municipal real estate management is one of the key factors to increase income, therefore it can be indispensable in achieving social and economic goals and enhancing gmina's development. The paper attempts to assess the share of income from real estate in local government revenues in Poland. In the article, the author shows the main areas in which municipal real estate management and property tax policy should be improved. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 258-269